The Neurocognitive Study for the Aging: Longitudinal Analysis on the Contribution of Sex, Age, Education and APOE ɛ4 on Cognitive Performance - Chadjikyprianou, Andreas; Hadjivassiliou, Marilena; Papacostas, Savvas; Constantinidou, Fofi (Frontiers in Genetics, 2021)
Objective: The effects of normal cognitive aging on executive functions (EF), Verbal Episodic Memory (VEM) and the contribution of age, sex, education, and APOΕ ε4 in a group of old Greek Cypriots across a five-year period were investigated. Design: NEUROAGE, the first project on cognitive aging in Cyprus, is a prospective longitudinal study with a rolling admission process. Participants are assessed at baseline and retested every 24–30 months. Subjects: 170 participants completed all three testing cycles; 86 men and 84 women with ages ranging between 60 and 88 years (mean = 73.21, SD = 5.84); education, 2–20 years (mean = 9.07, SD = 4.27). Results: Α Repeated Measures Multivariate Analysis of Covariance was conducted with one between-subject factor: sex; two covariates: age and education, while Time (time 1, time 2, time 3) served as a within – subject factor. Time did not have an effect on mini mental status examination in Greek (MMSE), EF or VEM. Also, sex had no effect on MMSE, EF and VEM. There was no time by sex interaction. Age and Education significantly predicted the EF performance, F(1, 168) = 11.23, p < 0.05; F(1, 158) = 90.03, p < 0.001 and VEM performance, F(1, 171) = 17.22, p < 0.001; F(1, 171) = 61.25, p < 0.001. Furthermore, there was a significant interaction effect between time and education, for EF, F(2, 167) = 7.02, p < 0.001. Performance of the APOE ε4 carriers did not differ on any of the above measures as compared to performance of non-carriers in this older adult group. Conclusion: Cognitively healthy adults maintained overall cognitive performance across the five-year period. Male and female participants performed similarly and the pattern of change over time was similar across the two sexes. Education was predictive of VEM and EF performance across time. Furthermore, those with higher education maintained higher levels of EF performance. APOE results did not differentiate performance at baseline. Implications of findings are discussed.